2015
DOI: 10.1097/scs.0000000000002017
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Goldenhar Syndrome from Craniofacial Microsomia

Abstract: Goldenhar syndrome is characterized by the typical features of craniofacial microsomia (CFM) with the addition of epibulbar dermoids and vertebral anomalies. The aim of this study is to examine the objective differences between patients carrying a diagnosis of Goldenhar syndrome to those diagnosed with CFM. Thus, we performed an Institutional Review Board-approved retrospective chart review on all patients who presented with a diagnosis of CFM or Goldenhar syndrome from January 1990 to December 2012. Demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 22 publications
0
19
2
2
Order By: Relevance
“…Of the 25 records included, 14 were retrospective studies 15,16,[18][19][20][21][22][23][24][25][26][27][28][29] , one was a prospective study 30 , and 10 were case series [31][32][33][34][35][36][37][38][39][40] . The prospective study also had a retrospective component, in which patient charts were reviewed for additional information.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 25 records included, 14 were retrospective studies 15,16,[18][19][20][21][22][23][24][25][26][27][28][29] , one was a prospective study 30 , and 10 were case series [31][32][33][34][35][36][37][38][39][40] . The prospective study also had a retrospective component, in which patient charts were reviewed for additional information.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…However, Vento et al refuted GS/OAVS as a subtype of CFM, as they found no association between these anomalies 15 . Tuin et al concluded that use of the term GS is inconsequential, as not all GS patients meet the diagnostic criteria 16 . Also, Caron et al recently concluded that there are no phenotypically distinct groups in the CFM spectrum 17 .…”
mentioning
confidence: 99%
“…Las personas con MHF y dermoides epibulbares se dice que tienen síndrome de Goldenhar (SG) o displasia oculoauriculo vertebral. La triada patognomónica del SG incluye MHF, dermo-lipoma y anormalidades esqueletales vertebrales 1,3 .…”
Section: Introductionunclassified
“…También, los pacientes considerados subjetivamente con diagnóstico de SG tenían una mandíbula más severamente afectada, deformación del tejido blando y eran más propensos a tener compromiso bilateral y macrostomia. Sin embargo, al examinar más apropiadamente las características objetivas del SG, el grado de severidad de casi todas las deformaciones crá-neo faciales de estos pacientes no eran significativamente diferentes 3 .…”
Section: Introductionunclassified
“…It is considered a variant of craniofacial (hemifacial) microsomia (CFM), a group of congenital malformations that occur during the embryonic development of the first and second branchial arches, which give rise to the ear, face and eyelids [3][4][5] . Therefore, patients present with the classic signs of CFM, such as unilateral asymmetric incomplete facial development, which may affect the mandible, maxilla, ears, soft tissues and nerves, as well as epibulbar dermoids and vertebral anomalies [6][7] .…”
Section: Introductionmentioning
confidence: 99%